Abdimas Penyuluhan Penggunaan Alat Elektrolisa Air Kepada Siswa SMA Bidang IPA Pelita Bangsa - Parlindungan Pandapotan Marpaung; Adi Setiawan; Laurentius Guntur (Yayasan Literasi Sains Indonesia, 2023)
Clean water has good quality water hardness and has been consumed for human mineral needs, containing the chemical elements of the mineral metals Sodium (Na), calcium (Ca), Chloride (Cl), nitrate (Na), magnesium (Mg), and Sulfate (Su) in units of milli-grams (mg) dissolved in a sample of Le Mineral rand drinking water in a 330 ml serving plastic bottle. In scientific outreach service activities for class XII students in the science field at SMA Pelita Bangsa Pamulang, a water electrolysis device was carried out with the aim of knowing the description of the precipitate of metal mineral chemical elements or chemical pollutant elements dissolved in groundwater samples. The methodology for community service counseling is carried out by using a water electrolysis device on groundwater samples to determine the description of the precipitate of metal mineral chemical elements or chemical pollutant elements dissolved in groundwater samples. The process of water electrolysis was carried out on groundwater samples in a glass container of water absorbing electrical energy with a capacity of 94.0 volts ac and an electric current of 0.287 amperes for a processing time of two (2) minutes. As a result of the electrolysis process of the groundwater samples, brown, orange and blackish precipitate occurred which indicated that there was a measure of the chemical element content of the dissolved metal minerals in the groundwater sample.